The Oxford encyclopaedia of South Asian Christianity - Hedlund, Roger E. (Oxford reference online premium, 2012)
The Oxford Encyclopaedia of South Asian Christianity covers the 2000-year old story of Christianity in India and its neighbouring countries. Looking at Sri Lanka, Bangladesh, Pakistan, Nepal, Bhutan, and Maldives, alongside India, as well as Myanmar, Afghanistan, and the global South Asian diaspora, the Encyclopaedia celebrates the trans-cultural, migratory, and unique nature of South Asian Christianity.